A Comparative Analysis of the Efficiency of Thermal and Electric Energy Production in the District Heating Systems - Berzan V.; Postolaty V.; Bikova Elena; Babich V. (Problems of the Regional Energetics, 2016)
In the base of the technical and economic indicators of the exploitation, an analysis of the efficiency of operation of Combined Heat and Power stations (CHP) in the district heating system at various loads during the year have been provided. The value of specific indicators of operation of the CHPs have been determined: a specific consumption of the fuel, the cost of the fuel per unit of energy produced, as well as the difference between the selling price of energy and acquisition costs of the fuel. As have been found, the optimization of CHP’s of the district heating loading during the year in the Chisinau municipality can offer an economic benefit amounted at 13-19 mln. lei MD in comparison with the current practice of CHP’s generation capacity use.